Numerical Prediction of Field and Seismic Behaviour of a Geogrid Reinforced Steep Slope - Castorina Silva Vieira (2012)
The paper presents a numerical study carried out with a two-dimensional finite difference program to model the field behaviour and the seismic response of a geogrid reinforced steep slope constructed in the North of Portugal. The reinforced slope has an extension of about 206.2 m and the reinforced soil area reaches a maximum height of about 19.6 m. The analysis of monitoring information and the numerical simulation of the construction are briefly presented. The seismic behaviour of this structure is analysed considering earthquake ground motions artificially generated. The results of the numerical simulation of the embankment construction fitted reasonably with the monitoring data. The numerical modelling of this reinforced steep slope under seismic loading showed a good performance. The residual reinforcement tensile forces remain smaller than the long term design strength of the geogrids. Since the structure is an overpass embankment, permanent vertical settlements can be the most disquieting factor. This paper is an extended version of a conference paper [1]